Business English Materials; What Should be Developed Related to the 21st Century Competencies - Pratama Irwin Talenta; Maria Dimitrij Angie Pavita (ELT-Lectura, 2022)
Learning outcomes can be achieved with suitable teaching materials. The integration and effectiveness of teaching materials greatly influence the successful implementation of Business English. The long-term goal of this research and development is to develop 21st-century Competency-based Business English materials. The design of this study used the research and development (R&D) of Borg and Gall (1983) with simplification into four stages, namely: introduction, development, trial test, and dissemination which were held within six months. The data collected is tested for validity through triangulation tests by conducting forum group discussions with experts and colleagues. The research subjects are lecturers and students of English at Universitas Nasional Karangturi. Months 1 – 2 are for conducting preliminary activities, months 3 – 4 are for designing the assessment draft, and months 5 – 6 are for testing and dissemination. The results of this study are Business English teaching materials, including Job Interviews, Business English conversations, Business English Podcast, English for Presentation, Curriculum Vitae, and Application Letters as preparation for professional career development. The stages and results of the research are recommended to be a reference for teachers, lecturers, developers of teaching materials, and researchers in developing and teaching business English, especially for professional career development with steps through material development, assessment, and evaluation. It can conclude that the 21st-century competency-based Business English teaching materials that are produced trigger students to be more active in communication have high creativity, critical thinking, and good cooperation, and the students can learn by combining practical business knowledge directly.